Time to Change the 'Change': Stigma and Support in Blogs about the Menopause - Keren Darmon (Gender a Výzkum)
This article empirically explores how women who are members of UK-based women-only networks for women working in the media and communications industries blog about the menopause, speciﬁcally Bloom (www.bloomnetwork.uk), Women in Advertising and Communications Leadership (www.wacl.info), and Women in Public Relations (www.womeninpr. org). The overarching research question in this paper is: How do women who are members of women-only networks for women working in communications blog about the menopause? I seek to answer this question by exploring whether the selected blog posts' texts on the websites of women-only networks have a feminist and/or postfeminist sensibility. Speciﬁcally, do they engender an individualistic approach and/or promote solidarity? Furthermore, I examine the texts for indications regarding the 'sources and solutions for gender inequality in the workplace' (Gill, Orgad 2015: 340) and ask: What can this tell us about the networks' position vis-à-vis the menopause, feminism, and postfeminism? Discourse analysis reveals an entanglement of feminist and postfeminist sensibilities in the narratives constructed in the blogs, which can be characterised by two main interpretative repertoires, Stigma and Support, the implications of which call for multilevel and multifaceted changes to support mid-life women in the contemporary media and communications workplace and beyond.